“Novo porvir”: literatura e cooperativismo em candunga e outros escritos de Bruno de Menezes - FELIX, Renan Brigido Nascimento (Universidade Federal do Pará, 2017)
The present dissertation aims to understand Literature and Cooperativism as two fundamental aspects of the social experience of the literate Bento Bruno de Menezes Costa (1893-1963). In this sense, his engagement in the field of arts was used as a starting point to the perception of a social subject who had made of the constitutive experiences of his works a huge space to reflect the condition of parense people. It is not merely an ornament what he expressed on the fictional texts and cultural reflexions, so the retraction many of his poetries dynamized and told about the confluence of a poet who made from his accumulated life experiences on his wanderings present issues in terms of a subject who not only went to the people, but was people himself. Therefore, when we analyse the cooperativist production of Bruno Menezes, we researched abundant sparse texts, even by the sequence of the years – first half of XX century, especially the 50´s – thru the deployment of his public activities commanding S.A.C. (Service of Assistance to Cooperativism) organ created by Para State Government in which he worked for ten years, from 1945 to 1955. We also consider that the work Candunga, published in 1954, constitutes an important space to the diffusion of Cooperativism doctrine once a fictional reflection has been conceded to such theme. The creation of “Colonia Novo Porvir1” by the end of the storyline established a different horizon to the peasants from Bragantine Zone in the Northeast of Para State through fomenting agricultural associacionism among them. Thus, when working with the execution of projects in this matter, he added ingredients such as political experience and perceptions about nature, considering important the historical changes in Amazonian spaces. The specialization grade he detained about this theme helped him to multiply the cooperativist actions, and then, to present practical results to Paraense society.